Edward Barton in Hungary: Arguments for travel as diplomatic service. Issue 4 (14th August 2019) - Kowalczyk, Tomasz
Abstract: This article examines the correspondence of the second English ambassador to the Ottoman Empire, Edward Barton (1562/3–98), pertaining to his controversial voyage into Hungary as part of Sultan Mehmed III's army in 1596. Barton travelled without prior permission from Queen Elizabeth I, prompting her anger that a Christian representative of England should travel as an active participant of an invading Muslim army. This article shows how Barton's writing constructed his involvement in the voyage not only as an important and desirable opportunity, but further as a transgressive travel experience which was essential to the development of a model of ambassadorial conduct which had to evolve to meet the new challenges of facilitating cross‐cultural diplomatic alliances. Prioritising rhetoric which rehearsed arguments that experiential travel knowledge was an essential and unique source of information, Barton attempted to shape the reception of his actions by relating his position in carefully constructed written accounts. This hitherto unexplored approach to Barton's correspondence allows us a deeper understanding of the extent to which his writing, as well as his actions, pioneered a new model of cross‐cultural diplomacy at a crucial point for Elizabethan 'foreign policy'.